Motor and integrative neurophysiology - Tikhonovska, M. A.; Sukhomlinova, I. E.; Ivanchenko, D. G.; Samura, I. B.; Tikhonovsky, O. V.; Voteva, V. E.; Тихоновська, Марина Анатоліївна; Сухомлінова, Ірина Євгенівна; Самура, Ірина Борисівна; Іванченко, Дмитро Григорович; Тихоновський, Олександр Володимирович; Вотєва, Ванда Євгенівна (Zaporozhye state medical university, 2016)
Students’ independent practical work is an important part of the syllabus in the course of Normal Physiology. It helps students to study this fundamental subject. Systematic independent work enables to reach the final goal in the students’ education. It is also important while preparing the students for their future clinical work with patients. This theoretical material, questions and tests will help students to get ready for the examination.
Моторна та інтегративна нейрофізіологія